Risk factors for physical domestic violence in a high-prevalence HIV setting: findings from Project Accept baseline data (HPTN-043) - Sebastian Kevany; Godfrey Woelk; Starley B. Shade; Michal Kulich; Janet M. Turan; Alfred Chingono; Stephen F. Morin (AOSIS, 2013)
Zimbabwe faces an acute generalized HIV/AIDS epidemic combined with rapidly deteriorating economic and political conditions, under which levels of domestic violence are on the rise. We aimed to determine possible demographic and behavioral factors associated with physical domestic violence in a rural setting in order to better inform both national and local domestic violence and HIV prevention policies. Using the Project Accept baseline data set, we selected demographic, socio-economic, and behavioral variables that might be associated with physical domestic violence based on a review of the literature. Univariate and multivariate analyses were carried out, and odds ratios (OR) were computed using logistic regression. Women reporting physical domestic violence were significantly more likely to report (i) a history of childhood domestic violence (OR=2.96, P<0.001), (ii) two or more lifetime partners (OR=1.94, P<0.001), (iii) some form of sexual abuse as a child (OR=1.82, not significant), and (iv) low or medium socio-economic status as measured by type of homestead (OR=1.4, P=0.04) than women who reported no experience of physical domestic violence. Married women were less likely to experience physical domestic violence than unmarried women (OR=0.65, P=0.011). Women at greatest risk of domestic violence include those with a personal history of violence or sexual abuse, multiple lifetime partners, and low or medium socio-economic status. Risk assessments and joint interventions for both domestic violence reduction and HIV prevention should target these population groups, which are effective both on the public health and global heath diplomacy levels.